Delay factors on the administration of thrombolytic therapy in patients diagnosed with acute myocardial infarction in a general hospital Factores que atrasan la administración de trombolítico en pacientes con diagnóstico de infarto agudo del miocardio atendidos en un hospital general Fatores que retardam a administração de trombolítico em pacientes com diagnóstico de infarto agudo do miocárdio atendidos em um hospital geral - Luis Antônio Muller; Eneida Rejane Rabelo; Maria Antonieta Moraes; Karina Azzolin (Universidade de São Paulo, 2008)
OBJECTIVE: To identify factors that delay the onset of thrombolysis in patients with acute myocardial infarction (AMI). METHODS: A cohort study was carried out with 146 patients, each diagnosed with AMI and subjected to thrombolytic therapy. The data was extracted from medical records between January 2002 and December 2004. RESULTS: The average age of the studied population was 57.5 ± 9 years, 64.4% were male. The average time between the onset of pain and arrival at the hospital was 254.7 ± 126.6 minutes, 28.1% used an ambulance for the trip to the hospital, the door-to-electrocardiogram time averaged 19.4 ± 7.3 minutes and the door-to-needle time was 51.1 ± 14.9 minutes. There was no significant difference between the time of arrival to the hospital and the method of transportation used (P= 0.81), and those seen by cardiologists and during the nightshift had a reduction in the door-to-needle time, respectively (P=0.014) and (P=0.034). CONCLUSIONS: Study results show that the delay in the search for medical service, and the long time taken from door-to-electrocardiogram and to reach the AMI diagnosis were the factors involved in the delay of thrombolytic treatment. OBJETIVO: Identificar los factores que retardan el inicio de la trombolisis en pacientes con IAM. MÉTODOS: Estudio de coorte, en 146 pacientes, con diagnóstico de IAM sometidos a la terapéutica trombolitica. Los datos fueron extraídos de prontuarios, entre enero de 2002 y diciembre de 2004. RESULTADOS: El promedio de edad fue de 57,5 ± 9 años y 64% eran del sexo masculino. El tiempo promedio transcurrido entre el inicio del dolor y la entrada al hospital fue de 254,7 ± 126,6 minutos; 28% utilizaron la ambulancia como medio de transporte; el tiempo promedio porta ECG (tiempo porta ECG: intervalo entre el ingreso del paciente al hospital y la realización del electrocardiograma) fue de 19,4 ± 7,3 minutos y el tiempo porta aguja de 51,1 ± 14,9 minutos (tiempo porta aguja: intervalo entre la entrada del paciente al hospital y la administración del trombolítico). No hubo diferencia significativa entre el tiempo de ingreso al hospital y los medios de transporte utilizados. Los pacientes atendidos por un médico cardiólogo y durante el turno de la noche tuvieron una reducción en el tiempo porta aguja, respectivamente, de (P=0,014) y (P=0,034). CONCLUSIONES: Los resultados del estudio demuestran que la demora en el ingreso al servicio médico, el tiempo porta electrocardiograma y el tiempo para diagnosticar el IAM, fueron los factores que determinaron el retardo de la administración del trombolítico. OBJETIVO: Identificar fatores que retardam o início da trombólise em pacientes com IAM. MÉTODOS: Estudo de coorte , com 146 pacientes, com diagnóstico de IAM submetidos à terapêutica trombolítica. Os dados foram extraídos de prontuários, entre janeiro de 2002 e dezembro de 2004. RESULTADOS: A média de idade foi de 57,5 ± 9 anos, 64% sexo masculino. O tempo médio entre o início da dor e a chegada ao hospital foi de 254,7 ± 126,6 minutos, 28% utilizaram a ambulância para o deslocamento, o tempo porta-eletrocardiograma médio de 19,4 ± 7,3 minutos e tempo porta-agulha de 51,1 ± 14,9 minutos. Não houve diferença significativa entre o tempo de apresentação ao hospital e o meio de transporte utilizado. Os pacientes atendidos por cardiologistas e no turno da noite tiveram uma redução no tempo porta-agulha, respectivamente (P=0,014) e (P=0,034). CONCLUSÕES: Os resultados do estudo demonstram que a demora na chegada ao serviço médico, tempo porta-eletrocardiograma e tempo para diagnosticar o IAM, foram os fatores envolvidos no retardo da administração de trombolítico.